Ankle-Foot Orthosis Made by 3D Printing Technique and Automated Design Software. (30th July 2017) - Cha, Yong Ho; Lee, Keun Ho; Ryu, Hong Jong; Joo, Il Won; Seo, Anna; Kim, Dong-Hyeon; Kim, Sang Jun
Abstract : We described 3D printing technique and automated design software and clinical results after the application of this AFO to a patient with a foot drop. After acquiring a 3D modelling file of a patient's lower leg with peroneal neuropathy by a 3D scanner, we loaded this file on the automated orthosis software and created the "STL" file. The designed AFO was printed using a fused filament fabrication type 3D printer, and a mechanical stress test was performed. The patient alternated between the 3D-printed and conventional AFOs for 2 months. There was no crack or damage, and the shape and stiffness of the AFO did not change after the durability test. The gait speed increased after wearing the conventional AFO (56.5 cm/sec) and 3D-printed AFO (56.5 cm/sec) compared to that without an AFO (42.2 cm/sec). The patient was more satisfied with the 3D-printed AFO than the conventional AFO in terms of the weight and ease of use. The 3D-printed AFO exhibited similar functionality as the conventional AFO and considerably satisfied the patient in terms of the weight and ease of use. We suggest the possibility of the individualized AFO with 3D printing techniques and automated design software.